Protection against over-indebtedness: appraising suitability and affordability assessment in Malaysia and South Africa - Ilias, Ibtisam @ Ilyana; Hassan, Rusni; Abu Bakar, Elistina; Kassim, Salina (Malaysian Consumer and Family Economics Association, 2023)
This study analyses mandatory suitability and affordability assessment embodied in the Guidelines on Responsible Financing issued by the Central Bank of Malaysia, focusing on conventional banks, Islamic banks and prescribed development financial institutions. It employed a doctrinal legal research methodology whereby relevant primary and secondary sources of law were meticulously analysed. This study also employed comparative legal research methodology whereby the approach adopted in South Africa was scrutinised and compared against the practice in Malaysia. This study found that the Guidelines on Responsible Financing play an essential role in ensuring responsible lending among the banks, Islamic banks, and prescribed development financial institutions in Malaysia. Based on the analysis conducted, several recommendations were proposed to bolster the existing regulatory approach in imposing suitability and affordability assessment. The outcome of this study is imperative in reducing the situation of over-indebtedness among Malaysians and reinforcing the responsible lending regime in Malaysia.